2020
DOI: 10.1186/s13012-020-0976-1
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of design stakeholders’ views of developing and implementing a registry-based learning health system

Abstract: Background: New opportunities to record, collate, and analyze routine patient data have prompted optimism about the potential of learning health systems. However, real-life examples of such systems remain rare and few have been exposed to study. We aimed to examine the views of design stakeholders on designing and implementing a US-based registry-enabled care and learning system for cystic fibrosis (RCLS-CF). Methods: We conducted a two-phase qualitative study with stakeholders involved in designing, implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…Stakeholders were selected using purposive criterion-based sampling to represent different levels of the social ecology of children’s cancer including parent advocates, multidisciplinary health care providers, members/leaders of key pediatric psycho-oncology professional organizations, and leaders in the pediatric healthcare policy [ 20 , 21 ]. Parental stakeholders were considered who had children with cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders were selected using purposive criterion-based sampling to represent different levels of the social ecology of children’s cancer including parent advocates, multidisciplinary health care providers, members/leaders of key pediatric psycho-oncology professional organizations, and leaders in the pediatric healthcare policy [ 20 , 21 ]. Parental stakeholders were considered who had children with cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The key features and contributions of qualitative approaches to engage stakeholders in participatory methods for designing and refining implementation strategies (i.e., gathering process data and explanatory outcome data from which practical ideas can be inductively derived from diverse groups of stakeholders) are well documented [ 18 , 19 ]. Typically, an implementation science framework is used to facilitate data collection from stakeholders and analyze and interpret their data to identify themes and create or modify implementation strategies [ 10 , 20 , 21 ]. Few research reports detail how stakeholder results informed and transformed initial iterations of implementation strategies, particularly in a long-standing program of research focused on health equity.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the priorities and concerns of both parties will facilitate realistic and attainable goals in the context of coproduction facilitated by technology-enabled data sharing [ 5 ]. For successful mHealth interventions, patient-generated health data must be both meaningful to patients and useful to clinicians [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported associations between the use of patient-generated health data and improved symptom control and quality of life [10][11][12][13][14], patient-clinician communication and satisfaction [15,16], reduced health care utilization, and increased survival [17][18][19][20]. Such an approach is not yet used in CF clinical practice, despite a strongly stated need by the CF patient community [21][22][23]. A previous assessment of preferences for remote collection and sharing of patient-generated health data among patients with CF or their caregivers reported that the majority are willing to share such data [24].…”
Section: Introductionmentioning
confidence: 99%
“…We believe this to be an innovative project in the field of developing a decision support tool using the principles of co-production and evaluating the experiences and reflections of those involved in the process. Studies have reported upon co-production as a method of increasing user involvement, primarily in the form of exploratory studies [24,25] or case study [26][27][28][29][30][31] reviews. However, there is a dearth of literature relating to the combined experience of a team of modelling researchers and stakeholders on iteratively co-producing a simulation decision support tool.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%